Chapter Przegonić chmury: komunikowanie wizji, misji i wartości na stronach WWW bibliotek akademickich - Banaszewski, Kamil; Bartosiak, Katarzyna (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
There are many uncertains about the future of academic libraries in contemporary debates. Dictated with changes in the environment as well as in education, they make the redefinition of university libraries necessary and the new formula for their identity is needed. Answers for following about mission and vision of libraries should be found: how do libraries see their future and their prospective role? could library image be shaped by mission and vision, plans and strategies, values and goals? could those affect the stakeholders’ evaluation? If so, whether and how are they communicated to the users? Do academic libraries use the communication and information potential of their own websites? Analyzing the web pages of the Polish public university libraries, the article examines whether and where the information about the mission, vision and values is placed on their web portals.